'Dogmas' for television drama: The ideas of 'one vision', 'double storytelling', 'crossover' and 'producer's choice' in drama series from the Danish public service broadcaster DR. Issue 2 (1st September 2013) - Redvall, Eva Novrup
This article traces the main concepts in the so-called production dogmas of the in-house drama department DR Fiction at the Danish Broadcasting Corporation (DR), which has recently produced acclaimed series such as Forbrydelsen/The Killing (2007–2012) and Borgen (2010–2013). The idea of putting the writer at the centre of the production process based on the concept of 'one vision' is highlighted as important to understanding the nature of the series from DR. The article discusses the concepts of public service 'double storytelling', organizing production based on notions of 'crossover' between the film and TV industry and 'producer's choice'. The article argues that while the strong talent behind the series and contextual aspects such as the recent interest in 'Nordic Noir' and new scheduling strategies for subtitled content by UK broadcaster BBC4 are important for understanding the international interest, major changes in the mode of production at DR Fiction since the late 1990s also need to be included in the understanding of the choice of content, the look and the recent success of several Danish series.